Laminin Coating Promotes Calcium Phosphate Precipitation on Titanium Discs in vitro - Kostas Bougas; Victoria Franke Stenport; Pentti Tengvall; Fredrik Currie (eJournal of Oral Maxillofacial Research, 2011)
Objectives: The objective of this study was to investigate the effect of a laminin coating on calcium phosphate precipitation on three potentially bioactive titanium surfaces in simulated body fluid.Material and Methods: Blasted titanium discs were prepared by alkali and heat treatment (AH), anodic oxidation (AO) or hydroxyapatite coating (HA) and subsequently coated with laminin. A laminin coated blasted surface (B) served as a positive control while a blasted non coated (B-) served as a negative control. Surface morphology was examined by Scanning Electron Microscopy (SEM). The analysis of the precipitated calcium and phosphorous was performed by Energy Dispersive X-ray Spectroscopy (EDX).Results: The thickness of the laminin coating was estimated at 26 Å by ellipsometry. Interferometry revealed that the coating process did not affect any of the tested topographical parameters on µm level when comparing B to B-. After 2 weeks of incubation in SBF, the alkali-heat treated discs displayed the highest calcium phosphate deposition and the B group showed higher levels of calcium phosphate than the B- group.Conclusions: Our results suggest that laminin may have the potential to be used as a coating agent in order to enhance the osseoinductive performance of biomaterial surfaces, with the protein molecules possibly functioning as nucleation centres for apatite formation. Nevertheless, in vivo studies are required in order to clarify the longevity of the coating and its performance in the complex biological environment.